Country Partnership Framework for the Union of Comoros for the Period of FY20-FY24 - World Bank Group (World Bank, Washington, DC, 2020)
The FY20-FY24 Country Partnership Framework for the Union of Comoros seeks to accompany the country in finding a sustainable growth path and building the resilience of its population against multidimensional shocks. The CPF will focus on building resilience, strengthening human capital and fostering inclusive growth, as well as addressing the urgent need arising from the impacts of COVID-19 and Cyclone Kenneth.